Perancangan Sistem Informasi Pencarian Alamat Rumah Sakit Di Kota Bekasi Berbasis WAP - Cepi Cahyadi (Jurnal Sistem Informasi, 2019)
Abstract - Current address retrieval information systems are only manually created through books or official documents such as drawing maps in the form of paper mounted on the wall or in official places in the Bekasi City neighborhood. Based on the description of the above problems, then made improvements in the field of information services. The manual address search information system will be developed into a digital (computerized) information system in the form of a Mobile Wireless Application Protocol (WAP) technology. This technology is created using srcipt html, xlm, and MySQL database. The purpose of this system planning is to provide convenience in the delivery of information searches the important addresses in the city of bekasi widely for the mobile phone users who can be accessed via the internet. Through the development of this system access to information can be done anytime and anywhere without having to deal directly with existing sources.